The impact of the UK governments spending review into the Feed in Tariff (FIT) on the installation on photovoltaic panels in the residential sector. Issue 2 (2014) - Amira Elnokaly; Benjamin A.J. Martin
<x xml:space="preserve"> Abstract </x> Purpose – In October 2011 the Government brought in measures to reduce the revenue provided by the Feed in Tariff (FIT) system. This change came under a lot of opposition due to the potential affects that it would have upon the industry. The purpose of this paper is to explore the potential benefits of the FIT and the impact that the Governments Comprehensive Spending Review had upon the industry and its uptake by the householders. Design/methodology/approach – For the study and to calculate the benefits of the FIT, a predictive modelling tool was built that could calculate the potential income and savings for a household. A photovoltaic (PV) installation was then monitored for over a year and the results of the predictive modelling tool were compared to actual results produced from the system to show how accurate the modelling tool was. The impacts of the Governments comprehensive spending review and the potential impacts in the industry were then calculated and discussed. Findings – The FIT is still a good incentive for people investing in PV. However, the reduction in the FIT may impact the "Rent a Roof" system and this in turn will impact most heavily on lower income families. The research also concluded that the changes in the political agenda have had a major impact on the FIT for both the industry and the community. Thus, the solar FITs will continue to be an attractive incentive in place to pay for heating through renewable means and thus ensuring reducing the own carbon footprint. Concomitantly, well‐developed ownership schemes need to be put in place. Originality/value – The reduction in the FIT was the right move by the Government as it should prevent the increase in energy bill prices which will affect the people without PV at this point in time. It also has been set so that it is still generous enough to encourage the industry and stimulate installation as there is still profit but not in a way that should put people off. The UK may just have to take time to realise that the FITs are still a good deal after the very generous tariff that preceded them.